High-resolution records of 10Be in endogenic travertine from Baishuitai, China: A new proxy record of annual solar activity?. (15th July 2019) - Xu, Hongyang; Miyahara, Hiroko; Horiuchi, Kazuho; Matsuzaki, Hiroyuki; Sun, Hailong; Luo, Weijun; Zheng, Xiangmin; Suganuma, Yusuke; Wang, Shijie; Zhou, Limin
Abstract: The accurate reconstruction of past solar activity is a prerequisite for assessing the role of solar forcing on climate variations. Cosmogenic 10 Be, produced by galactic cosmic rays and stored in natural archives such as ice cores and lake sediments, has been shown to be the most reliable as an indicator of past solar activity, although reconstructions at a higher, annual, resolution have remained elusive due to dating imprecision and uncertainties concerning the effect of depositional processes. Here, we employ a methodology that facilitates the annual reconstruction of past cosmic-ray and solar activity variations. An annual 10 Be record is assembled from an endogenic travertine in Baishuitai, China, covering the period 2001–2016 CE. We demonstrate that the effect of depositional processes when 10 Be is incorporated into travertine can be accounted for using the associated 9 Be and potassium (K) contents, and that the resulting corrected 10 Be content significantly correlates with the modeled global 10 Be production rates with a time lag of 1.5–2.5 years. Our results from the Baishuitai endogenic travertine suggest that the 10 Be record in such carbonate sediments has considerable potential as a high resolution proxy for past cosmic-ray and solar activity variations. Graphical abstract: Image 1 Highlights: 10 Be in travertine has a high potential as a proxy for solar activity in the past. Climatological impact on 10 Be deposition can be corrected using 9 Be and K content. Corrected modern 10 Be record significantly correlates to global 10 Be production rate.